Menjaga Ruh Pancasila: Peran Kritis Kegiatan Kemahasiswaan di Tengah Arus Globalisasi - Intan Sri Ningrat (RETORIKA: Journal of Law, Social, and Humanities, 2023)
This study aims to: (1) identify the challenges of globalization to the understanding of Pancasila, (2) examine the critical role of student activities in strengthening the resilience of its values, and (3) formulate optimization strategies. Using a qualitative approach of comparative case studies on extra-campus organizations PMII and IPNU-IPPNU at UNU NTB, data were collected through observation, interviews, and document analysis. The results of the study show: (1) The challenges of globalization emerge as individualism, value confusion, and disruption of digital authority; (2) The critical role is realized through two complementary models: PMII as a critical-transformative filter and IPNU-IPPNU as a critical-cultural anchor, which together form an ecosystem of ideological resilience; (3) The optimization strategy is formulated within the framework of the tridharma including a dialogic curriculum, productive digital literacy, and project-based collaboration. This study recommends the need for structured intervention, the active role of universities as facilitators, and the repositioning of student organizations as strategic partners to produce leaders with contextual Pancasila characters.